(untitled) (Acta Scientiarum. Agronomy, 2024)
Proper potassium (K) fertilization management is crucial for optimizing yield and minimizing environmental impacts in colored fiber cotton cultivars, particularly in semiarid regions. This study aimed to assess the efficiency of K use by colored cotton cultivars under K fertilization in a semiarid region. Two experiments were conducted in 2019 and 2021, representing two agricultural seasons. The experimental design employed randomized blocks with split plots and four replications. The main plots consisted of five randomized K doses (0, 60, 120, 180, and 240 kg ha-1 of K2O), while subplots included four cultivars of colored cotton (BRS Rubi, BRS Safira, BRS Topázio, and BRS Verde). The results revealed that BRS Rubi exhibited superior agronomic efficiency with a dose of 60 kg ha-1 of K2O in both agricultural seasons. The maximum efficiency of K use by colored cotton cultivars was achieved with a dose of 240 kg ha-1 of K2O in the semiarid region of Brazil. The cultivars BRS Rubi and BRS Topázio demonstrated the highest use efficiency. Furthermore, BRS Topázio displayed the highest K accumulation in plant shoots during both seasons.